Psychological symptomatology of the phenomenon «emotional burnout» of teenagers: empiric researches - Vashchenko, I.; Kondratska, L.; Nishkur, D. (My University, 2017)
The article presents the results of empirical research of psychological symptoms of «emotional burnout» phenomenon of teenagers. There have been identified and analyzed the external factors that provoke emotional burnout of teenagers such as: chronically tense psycho-emotional activity; destabilizing organization of learning activities; increased responsibility for the performed functions; adverse psychological atmosphere in the school; psychologically heavy contingent, with which teenager communicates; adverse psychological atmosphere at home. There have been empirically determined internal factors that contribute to emotional burnout: emotional tendency to rigidity; intense interiorization (perception and experience) circumstances of training activities; moral defects and personality disorientation. It is shown that emotional burnout of teenagers as a syndrome is characterized by following features: behavior change; thinking change; feelings change; health change. It was identified direct dependence between high levels of anxiety and conflict of teenagers’ father and mother; frequency of conflicts in the family; the depth of the conflict; reconciliation with parents. «Obstacles» in the development of emotional contact with teenagers were concretized: inability to control emotions, their dose, inflexibility, lack, opacity emotions and reluctance to contact with people. The features of young individual, which leads him to deformation, are those: emotional instability, characterized by mood instability, high personal anxiety, tendency to events dramatization, demonstrativeness, self-centeredness; psychasthenic traits, impulsiveness, conflictness, inadequate self-esteem.
Keywords: емоційна сфера; емоційне вигорання; сімейні конфлікти; підліткова криза; самооцінка; тривожність; конфліктність; агресивність; emotional sphere, emotional exhaustion, family conflicts, teenage crisis, self-rating, uneasiness, conflictness, aggression; эмоциональная сфера, эмоциональное выгорание, семейные конфликты, подростковый кризис, самооценка, конфликтность, тревожность, агрессивность